Unveiling cryptic diversity of the anemonefish genera Amphiprion and Premnas (Perciformes: Pomacentridae) in Thailand with mitochondrial DNA barcodes - na Ayudhaya, Pradipunt Thongtam; Muangmai, Narongrit; Banjongsat, Nuwadee; Singchat, Worapong; Janekitkarn, Sommai; Peyachoknagul, Surin; Srikulnath, Kornsorn (Agriculture and Natural Resources, 2017)
The genera Amphiprion and Premnas comprise the common anemonefish that are widely distributed in tropical areas. Species identification of these two genera is difficult due to high, intraspecific, morphological variation. Recently, DNA barcoding has been employed as an efficient tool that uses a short genetic marker in an organism's DNA to enable the identification and recognition of cryptic species. This study applied three regions of mitochondrial DNA-cytochrome c oxidase I (COI), cytochrome b (Cytb) and 16S rRNA-as DNA barcodes for species identification of seven species of Amphiprion and one species of Premnas in Thailand. Three species-delimitation methods-general mixed Yule-coalescent (GMYC), automatic barcoding gap detection (ABGD) and a Bayesian implementation of the Poisson tree processes model (bPTP)-were also used to estimate the number of species. An overlap was found between the intra- and inter-specific genetic divergence values in Cytb and 16S rRNA, but not for the COI data. This indicated that COI was the most effective for identifying different anemonefish species. A three-gene phylogenetic analysis and species-delimitation methods based on both COI and Cytb data suggested cryptic diversity in Amphiprion clarkii, A. percula, A. ocellaris and Premnas biaculeatus. Different distributions were found also for two cryptic species of A. clarkia-one restricted to the Gulf of Thailand and the other to the Andaman Sea. The results confirmed the efficiency of COI as a suitable marker for species identification of anemonefish.